The Impact of TATO and DER on ROA in IDX 2019-2023 Property and Real Estate Companies - Hanifa Sri Nuryani (Komunitas Dosen Indonesia, 2024)
This study was carried out at publicly listed property and real estate companies on the Indonesia Stock Exchange. The objective of this study is to examine and evaluate the impact of total asset turnover and debt to equity ratio on return on assets in Property and Real Estate Companies that are listed on the IDX from 2019 to 2023. The research methodology utilized in this study adopts a causal approach, specifically employing a quantitative and descriptive research design. The study included a total of 78 companies, selected using purposive selection technique, resulting in a sample size of 54 companies. The study employed the multiple linear regression approach and conducted classical assumption checks for analysis. The findings of this study suggest that the Total Asset Turnover and Debt to Equity Ratio significantly impact the Return on Assets (ROA) in Property and Real Estate companies listed on the Indonesia Stock Exchange between 2019 and 2023. The TATO has a moderately favorable influence on the return on assets (ROA), whereas the debt-to-equity ratio (DER) has a substantial and adverse effect on ROA. These findings have significant consequences for individuals and organizations involved in the property and real estate industry, highlighting the crucial role of strategic asset management and financial structuring in influencing firm performance. This research makes a valuable contribution to scholarly discussions and provides practical insights for professionals seeking to improve financial performance in the ever-changing Indonesian real estate market.